Comparison of detection limit in fiber-based conventional, amplified, and gain-clamped cavity ring-down techniques - Sharma, Kavita; Abdul Khudus, Muhammad Imran Mustafa; Alam, Shaif-ul; Bhattacharya, Shanti; Venkitesh, Deepa; Brambilla, Gilberto (Elsevier, 2018)
Relative performance and detection limit of conventional, amplified, and gain-clamped cavity ring-down techniques (CRDT) in all-fiber configurations are compared experimentally for the first time. Refractive index measurement using evanescent field in tapered fibers is used as a benchmark for the comparison. The systematic optimization of a nested-loop configuration in gain-clamped CRDT is also discussed, which is crucial for achieving a constant gain in a CRDT experiment. It is found that even though conventional CRDT has the lowest standard error in ring-down time (Δτ), the value of ring-down time (τ) is very small, thus leading to poor detection limit. Amplified CRDT provides an improvement in τ, albeit with two orders of magnitude higher Δτ due to amplifier noise. The nested-loop configuration in gain-clamped CRDT helps in reducing Δτ by an order of magnitude as compared to amplified CRDT whilst retaining the improvement in τ. A detection limit of 1.03×10−4 RIU at refractive index of 1.322 with a 3 mm long and 4.5 μm diameter tapered fiber is demonstrated with the gain-clamped CRDT.